2020
DOI: 10.1371/journal.pone.0229068
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of a novel neuroprotectant, KUS121, in patients with non-arteritic central retinal artery occlusion: An open-label, non-randomized, first-in-humans, phase 1/2 trial

Abstract: Kyoto University Substance (KUS) 121, an ATPase inhibitor of valosin-containing protein, is a novel neuroprotectant. We tested the safety and effectiveness of KUS121 in patients with acute central retinal artery occlusion (CRAO). We conducted an investigator-initiated, firstin-humans, phase 1/2 clinical trial. Nine patients with non-arteritic CRAO symptoms lasting for 4-48 h were enrolled. These patients received daily intravitreal injections of KUS121 for 3 days: 25 μg (low-dose) in the first three patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Recently, a new neuroprotective drug (KUS121) has been under clinical trial for CRAO [ 66 ]. CRAO brings acute damages to nerve cells caused by arterial occlusion, and KUS121 is expected to inhibit dysfunction of intracellular organelles, mainly the smooth endoplasmic reticulum, and maintain their activities.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new neuroprotective drug (KUS121) has been under clinical trial for CRAO [ 66 ]. CRAO brings acute damages to nerve cells caused by arterial occlusion, and KUS121 is expected to inhibit dysfunction of intracellular organelles, mainly the smooth endoplasmic reticulum, and maintain their activities.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the present study, administration of KUS121 has been shown to mitigate pathologies by reducing ER stress and cell death in several animal models representing conditions such as retinitis pigmentosa 15 , myocardial infarction 16 , ischaemic stroke 20 , and Parkinson’s disease 22 . Moreover, KUS121 has been tested in phase I/II clinical trial for acute central retinal artery occlusion and shown to be safe and efficacious 23 , thereby indicating its promising candidature in the clinical therapy to inhibit the development of PTOA following cartilage injury and other conditions that have been discussed earlier.…”
Section: Discussionmentioning
confidence: 99%
“…KUS121 has been shown to protect against cell death in animal models of ocular diseases including retinitis pigmentosa 15,17 , macular degeneration 18 , and glaucoma 19 , ischemic diseases including myocardial infarction 16 , ischemic stroke 20 , and retinal artery occusion 21 and Parkinson's disease 22 . Moreover, phase I/II clinical trials show its safety and potential effectiveness in patients with non-arteritic central retinal artery occlusion 23 . ER stress has also been shown to contribute to the degeneration of chondrocytes in the articular cartilage; excessive ER stress induces chondrocyte death in parallel with the severity of OA [24][25][26][27][28] .…”
mentioning
confidence: 99%
“…We recently reported the therapeutic effects of KUS121 on post-traumatic cartilage damage in rats 18 . Among KUSs, KUS121, which has strong protective effects, was safe and effective in a phase 1/2 clinical trial in patients with central retinal artery occlusion 26 .…”
Section: Discussionmentioning
confidence: 99%